Evaluation of robotic-assisted mitral surgery in a contemporary experience. Issue 6 (June 2022) - Agnino, Alfonso; Graniero, Ascanio; Villari, Nicola; Roscitano, Claudio; Gerometta, Piersilvio; Albano, Giovanni; Anselmi, Amedeo
Abstract : Aims: To evaluate the safety/effectiveness of a recently established robotic-assisted mitral surgery program. Methods: Cohort study with prospective collection of clinical data of 59 consecutive recipients (May 2019–August 2021) of robotic-assisted (fourth-generation platform, DaVinci X) mitral valve repair for degenerative disease, using a totally endoscopic technique. Patients' selection was based on defined anatomical and clinical criteria. We established a dedicated multidisciplinary protocol to facilitate postoperative fast-tracking, and a systematic in-house clinical and echocardiographic follow-up at 3, 6, and 12 postoperative months. Results: All patients (89.8% men, average age 58 ± 12 years) received mitral valve repair; there was no operative mortality, one conversion to sternotomy (1.7%) and one stroke (1.7%). Extubation within the operative theater occurred in 28.8%; average mechanical ventilation time and ICU stay was 2.8 ± 4.1 and 32.5 ± 15.8 h (after exclusion of one outlier, learning-curve period, suffering from perioperative stroke); average postoperative hospital stay was 6.8 ± 3.4 days and 96.6% of patients were discharged home. One patient was transfused (1.7%); there were no other complications. Follow-up revealed stability of the results of mitral repair, with one (1.7%) persistent (>2+/4+) mitral regurgitation, and stability of coaptation height over time. We observed optimal functional results (class I was 98% at 3 months and 96% at 12 months). Quarterly case load consistently increased during the experience. Conclusion: This initial experience suggests the reliability and clinical safety of a recently established local robotic-assisted mitral surgery. This strategy can facilitate faster postoperative recovery, and its positioning in the therapeutic armamentarium needs to be defined.